Iron Replacement in Hemodialysis Patients– A Review - Basit, Bilal; Fayyaz, Risha (Pakistan Journal of Kidney Diseases, 2021)
Anemia is a prevalent condition among all stages of chronic kidney diseases. Iron deficiency anemia is a common occurrence in all the stages and has important implications in terms of patient care and cost effectiveness. In this article we highlight the importance of understaning the iron metabolism and its management.